Application of the District Magnitude Principle in Determining Electoral Districts and Allocation of Seats (Study at the General Election Commission of Lampung Province) - Fajar, Gilang Aditia; Harjo, Budi; Warganegara, Arizka (CV. Rayyan Dwi Bharata, 2024)
This research aims to find out and describe the determination of electoral districts and the allocation of seats in the regional people's representative council of Lampung Province in 2024 according to the district magnitude principle. This research uses a descriptive method with a qualitative approach. Informants were selected through purposive sampling technique. Data collection techniques using in-depth interviews and documentation. The data collected was analyzed using the principles for structuring electoral districts and seat allocation as stated by Lisa Handley and Article 185 of Law No. 7 of 2017 concerning Elections. The research results show that the application of the district magnitude principle in determining electoral districts and seat allocation is in accordance with the established principles. The principle of impartiality by existing and preparing electoral district plans and then public testing. The principle of equality through the implementation of opovov, however the number of electoral districts needs to be evaluated so that proportionality is met. Principle of Representation by considering historical, socio-cultural, customs, group diversity aspects, conducting FGDs with academics, community leaders, media, government and political parties. The principle of non-discrimination does not differentiate between race, skin color, language, religion and status. Transparent principles by involving stakeholders, implementing Si Dapil, and socializing activities through the website.